Murders Committed by Women in Lithuania: an Analysis of Šiauliai District Court Cases of 1922–1940 - Každanas, Robertas (Acta humanitarica academiae Saulensis, 2025)
The aim of this paper is to analyse the homicide cases committed by women in Lithuania, which were examined in Šiauliai District Court of the first instance. Since its establishment in 1922, the jurisdiction of Šiauliai District Court included approximately one-third of the interwar Lithuania territory and population. Therefore, its surviving material is significant to the reconstruction of features of the crime in Lithuania, which have not been included in official statistical publications. The definition of criminal acts and sanctions were regulated by the Penal Code of the Russian Empire, which was enacted in 1918 and was valid until 1940 with slight modifications in order not to conflict with the constitution and laws of the State of Lithuania. Deprivation of life was described in the 22nd chapter of the Penal Code and specified the killing of a person, the killing of a newborn, assisted suicide, and the destruction of a fetus. The research of 163 court cases and 115 convicted women made it possible to reveal the most common circumstances of murdering a person, to identify what were the motives that prompted the woman to commit the crime, and what was the prevailing social characteristic of female criminals. The investigation found that 87 women were convicted of neonaticide, causing asphyxiation of a baby. Another 20 cases involved intentional homicide and 8 involved involuntary manslaughter of an adult.